Aboveground biomass estimation of wetland vegetation at the species level using unoccupied aerial vehicle RGB imagery - Zhou, Rui; Yang, Chao; Li, Enhua; Cai, Xiaobin; Wang, Xuelei (Frontiers in Plant Science, 2023)
Wetland vegetation biomass is an essential indicator of wetland health, and its estimation has become an active area of research. Zizania latifolia (Z. latifolia) is the dominant species of emergent vegetation in Honghu Wetland, and monitoring its aboveground biomass (AGB) can provide a scientific basis for the protection and restoration of this and other wetlands along the Yangtze River. This study aimed to develop a method for the AGB estimation of Z. latifolia in Honghu Wetland using high-resolution RGB imagery acquired from an unoccupied aerial vehicle (UAV). The spatial distribution of Z. latifolia was first extracted through an object-based classification method using the field survey data and UAV RGB imagery. Linear, quadratic, exponential and back propagation neural network (BPNN) models were constructed based on 17 vegetation indices calculated from RGB images to invert the AGB. The results showed that: (1) The visible vegetation indices were significantly correlated with the AGB of Z. latifolia. The absolute value of the correlation coefficient between the AGB and CIVE was 0.87, followed by ExG (0.866) and COM2 (0.837). (2) Among the linear, quadratic, and exponential models, the quadric model based on CIVE had the highest inversion accuracy, with a validation R 2 of 0.37, RMSE and MAE of 853.76 g/m 2 and 671.28 g/m 2 , respectively. (3) The BPNN model constructed with eight factors correlated with the AGB had the best inversion effect, with a validation R 2 of 0.68, RMSE and MAE of 732.88 g/m 2 and 583.18 g/m 2 , respectively. Compared to the quadratic model constructed by CIVE, the BPNN model achieved better results, with a reduction of 120.88 g/m 2 in RMSE and 88.10 g/m 2 in MAE. This study indicates that using UAV-based RGB images and the BPNN model provides an effective and accurate technique for the AGB estimation of dominant wetland species, making it possible to efficiently and dynamically monitor wetland vegetation cost-effectively.